Platform-Based Brand Voice: Analisis Wacana Gaya Komunikasi Brand Skingame di Media Sosial - Icha Nur Lailatul Alfin; Putu Riana Artyanti Putri (Jurnal Nomosleca, 2025)
This study examines the differences in communication styles of the Skingame brand across two social media platforms, Instagram and Twitter/X, with a focus on how the brand adapts its brand voice to suit its audience characteristics. The objectives of this study are (1) to identify how Skingame's communication styles are displayed through Instagram and Twitter/X content, and (2) to analyze these adjustments through the perspectives of Communication Accommodation Theory (CAT) and Social Identity Theory (SIT). The study uses a qualitative approach with the van Dijk discourse analysis model, which includes analysis of text structure, social cognition, and social context. The results show that on Instagram, Skingame displays a formal-casual persona with informative content and consistent visual branding, while on Twitter the brand is more relaxed, humorous, and interactive, using slang, memes, and quick responses to trends. The analysis shows that these differences in communication styles are a form of convergence (CAT) according to the ecology of each platform, while simultaneously forming a dual social identity (SIT): professional on Instagram and relatable on Twitter. Thus, this study emphasizes the importance of platform-based communication strategies in building and strengthening a brand's social identity in the digital era.